ความสัมพันธ์ระหว่างความสามารถในการทำกำไรกับอัตราผลตอบแทน จากส่วนต่างราคาหุ้นของบริษัทในหมวดธุรกิจพาณิชย์ที่จดทะเบียน ในตลาดหลักทรัพย์แห่งประเทศไทย - สิงห์ศักดิ์ตระกูล ดวงใจ; ลิ่วคุณูปการ นิรันดิ์เกียรติ; กุฏิภักดี ฐานกุล; มั่นเศรษฐวิทย์ ศิษฏ์ธวัช (Al-HIKMAH Journal, 2019)
The objective of this study was to study the relationship between profitability and rate of return in capital gain yield of business and commerce sectors listed in the Stock Exchange of Thailand. The research was conducted by analyzing the data collected from 15 companies and interview Yala local investors. The results of this study were as follows: 1) The Profitability Ratio of Return on Asset(ROA) had the negative relationship with rate of return in capital gain yield of COL Public Company Limited at a significant level of 0.05. 2) The Profitability Ratio of Return on Equity(ROE) had the negative relationship with rate of return in capital gain yield of COL Public Company Limited at a significant level of 0.05. 3) The Profitability Ratio of Net Profit Margin(NPM) had the negative relationship with rate of return in capital gain yield of COL Public Company Limited at a significant level of 0.05. 4) The Profitability Ratio of Operating Income Margin(OIM) had the negative relationship with rate of return in capital gain yield of COL Public Company Limited at a significant level of 0.05 and had positive relationship with rate of return in capital gain yield of Mida Assets Public Company Limited at a significant level of 0.05. 5) The Profitability Ratio of ROA, ROE, NPM and OIM of business and commerce sectors had no influence on rate of capital gain yield of business and commerce sectors listed in the Stock Exchange of Thailand. The results of interviews revealed that factors affecting SET business and commerce group index include domestic and global economic, the reliability of consumers and government policy on economic promoting. In case of the negative tendency of future economy, the assumption includes the most securities will decrease or in case of the positive tendency of future economy, the assumption includes the most securities will increase.